2022
DOI: 10.3390/polym14214490
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Strengthening Mechanism of Ultrastrong and Tough Cellulosic Materials

Abstract: Superior strong and tough structural materials are highly desirable in engineering applications. However, it remains a big challenge to combine these two mutually exclusive mechanical properties into one body. In the work, an ultrastrong and tough cellulosic material was fabricated by a two-step process of delignification and water molecule-induced hydrogen bonding under compression. The strong and tough cellulosic material showed enhanced tensile strength (352 MPa vs. 56 MPa for natural wood) and toughness (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It can be observed that SMAHC laminates (B-2-4) have the highest bending performance. The flexural performance of SMAHC laminates is given in Table 4 [ 27 ]. The flexural strength of SMAHC laminates (B-2-2/4/6) is 368.62 MPa, 369.17 MPa and 318.73 MPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that SMAHC laminates (B-2-4) have the highest bending performance. The flexural performance of SMAHC laminates is given in Table 4 [ 27 ]. The flexural strength of SMAHC laminates (B-2-2/4/6) is 368.62 MPa, 369.17 MPa and 318.73 MPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results of the numerical tests showed a high compliance with the results of the experimental studies. Han et al [ 27 ] used the finite element analysis (FEA) method to simulate the mechanical behaviors of ultrastrong and tough bulk material under a tensile state. FEA results showed that water molecules played an active role in fabricating strong and tough materials, by plasticizing and forming hydrogen bonding among cellulose nanofibrils.…”
Section: Introductionmentioning
confidence: 99%
“…The natural anisotropic porous structure of wood allows for the transport of water and ions from the roots to the crown, which is essential for improving the ion migration efficiency of MEG. Wood is mainly composed of cellulose, hemicellulose, and lignin [ 23 , 24 ]. The hydroxyl and carboxyl groups in cellulose molecular chains are the main reactive sites in wood-based materials [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose is a linear biopolymer formed by glucose units connected by β-1,4-glycosidic bonds, and mainly exists in plants, animals, algae, and fungi [9][10][11][12][13][14][15]. Nanocellulose (NC) is a cellulosic material with at least one dimension within the nanometer size.…”
Section: Introductionmentioning
confidence: 99%